Implikacje stosowania dyskonta do oceny efektywności inwestycji ochrony środowiska - Baron, Magdalena (Implications of Discounting in Relation to Effectiveness of Environmental Projects Assessment, 2005)
The study reanalysis the fundamental determinants of discounting, especially in the light of environmental factors. The reanalysis arises partly because of the alleged "discrimination" of conventional discount rate selection processes against the interests of the environment and partly because concern for natural environments associated with an ethical stance on intergenerational justice. The study also indicates an alternative to lowering discount rates, to integrating environmental concerns into decision-making. One important way of doing so, is to ensure that the environmental effects of investments are valued in economic terms. The second one is to integrate a sustainability requirement into the analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 11-21